High-temperature superconductors - Saxena, Ajay Kumar (Springer Series in Materials Science, 2012)
This book presents the current knowledge about superconductivity in high Tc cuprate superconductors. There is a large scientific interest and great potential for technological applications. The book discusses all the aspects related to all families of cuprate superconductors discovered so far. Beginning with the phenomenon of superconductivity, the book covers: the structure of cuprate HTSCs, critical currents, flux pinning, synthesis of HTSCs, proximity effect and SQUIDs, possible applications of high Tc superconductors and theories of superconductivity. Though a high Tc theory is still awaited, this book describes the present scenario and BCS and RVB theories. The second edition was  significantly extended by including film-substrate lattice matching and buffer layer considerations in thin film HTSCs, brick-wall microstructure in the epitaxial films, electronic structure of the CuO2 layer in cuprates, s-wave and d-wave coupling in HTSCs and possible scenarios of theories of high Tc superconductivity.